Memahamkan Akuntansi Dengan Penalaran Dan Pendekatan Sistem - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT Accounting equation is a useful tool for teaching accounting. However, its inappropriate use at the beginning of introductory accounting course tends to inhibit students' understanding of and reasoning for accounting process. It is dcult for students to link the accounting equation as an abstraction of reality with the real world counterpart it represents. This difficulty is likely to block students' reasoning for accepting further materials presented to them. To avoid such a dysfunctional behavior, an alternative approach that makes more sense should be introduced in accounting teaching and learning. In this article, to round up the earlier one (Suwardjono, 1999), the author proposes and describes a system approach to introducing accounting to beginners. This alternative approach brings students to follow logically and conceptually a step-by-step process of developing accounting systems from the simplest or embryonic to the most sophisticated and computerized ones. In each step, the underlying concepts and reasoning for refining the systems are discussed along with the teaching strategies and techniques of explaining them to students. The author believes that this approach will give more benefits to students especially to nonaccounting major students. Key words: introductory accounting, accounting equation, system approach, systems development process. embryonic system, computerized systems